Gender inequality in job quality. What has happened in Spain during the recession? - Pilar Ficapal-Cusí; Ángel Díaz-Chao; Joan Torrent Sellens (Internet Interdisciplinary Institute, Open University of Catalonia, 2016)
Through a representative sample of 5,381 (3,079 men and 2,302 women) and 4,925 (2,719 men and 2,206 women) employees in 2008 and 2010, and a using two-stage structural equation model, this article empirically analyses the multi-dimensional determinants (direct effects) of gender-related job quality in Spain. The research revealed four main results. First, despite the economic crisis, job quality in Spain had improved over the analysis period. Second, the improvement in job quality during the crisis was more favourable to men than it was to women. Third, the gender differences in the explanation of job quality during the crisis increased considerably in favour of men. Fourth, this increase in gender difference in job quality in favour of men is explained by a worsening of 4 of the 5 explanatory dimensions thereof: intrinsic job quality; work organisation and workplace relationships; working conditions, work intensity and health and safety at work; and extrinsic rewards. Only inequality in the work-life balance dimension remained stable from 2008 to 2010. In terms of employment and gender equality public policy our research results suggest two important conclusions. In the first place, the importance of paying much greater attention to working environment and social relation dimensions in gender-related employment public policies. Second, gender equality public policy should also address new problems associated with the accelerated changes at work. In particular, the different job quality problems between highly skilled and less skilled working men and women, the link between gender gap and occupations, and the need to consider the different institutional regimes and organised labour to overcome gender-related job inequalities.
Keywords: J16; J28; J53; 330; Gender inequality; job quality; Economic crisis; Structural equation modelling